MODEL PENGELOLAAN EKOSISTEM PERAIRAN DANGKAL PULAU SEMAK DAUN KEPULAUAN SERIBU DALAM KERANGKA PEMBANGUNAN SEA FARMING BERKELANJUTAN - F.B. ARIEF; K. SOEWARDI; R. DAHURI; S. HADI; L. ADRIANTO (Akuatik: Jurnal Sumberdaya Perairan, 2009)
The aim of this research is not only to find the carrying capacity and economic of Sea Farming management but also to build the model of shallow water ecosystem at Semak Daun Island. For that purpose, the researcher uses the amount of Serranus sp as an indicator with two kinds of assessment methods. The first method is denseness assessment. Using this method the amount of Serranus is in between 1575 and 1890 fish for year. The second method is tranfer of energy in the trophic level. By this method, the researcher find that the amount of Serranus lays in the wider range than the first one it is from 1575 to 7875 fish for year. According to the result of simulating the model for all scenarios in 10 years, the highest income get from the third scenario, Rp 4,074,830,000.00, with the proportion of KJA (cage culture) and Sea Ranching fund is 75% and 25%, there is aninstitution with Rp 50,000.00 as a monthly fee. Meanwhile, the 25th scenario only give Rp 806,130,000.00 as the income with the proportion of KJA (cage culture) and SR fund is 25% and 75% without an institution and only Rp 10,000.00 monthly fee.